Manajemen Kesehatan Ternak Sapi Melalui Pemberian Obat-Obatan Dan Multivitamin - Yolada Gebze; Denvy Meidian Daoed (CV. SINAR HOWUHOWU, 2026)
Tanah Miring District is one of the areas with the largest beef cattle population in Merauke Regency. Despite its significant regional potential, the knowledge of local smallholder farmers remains relatively limited, and their business practices remain traditional. A good understanding of livestock health management and mating regulations has a direct impact on optimizing livestock productivity. To address these challenges, the Musamus University community service team, in collaboration with local animal health officers, implemented an intervention program through initial observation, followed by counseling and the provision of medication and multivitamins. The results of the activity demonstrated a high level of urgency and need among farmers for educational programs on health management and regular mating to achieve optimal business profitability. Overall, this program has proven effective in transforming livestock farmers' knowledge and is projected to boost beef cattle productivity in Tanah Miring District, Merauke Regency.